Pengaruh Kualitas Pelayanan Dan Citra Perusahaan Terhadap Kepuasan Konsumen: Studi pada perusahaan jasa pengiriman di Kota Bandung - Tika Aswati; Anton Tirta Komara; Rd. Okky Satria; Nita Yura Roslina (Center of Research, STIE Pasundan, Bandung, Indonesia., 2022)
This study aims to determine the magnitude of the influence of service quality and corporate image on customer satisfaction at one of the delivery service companies in the city of Bandung. Respondents are customers who use delivery services as many as 90 customers. Researchers used path analysis techniques to determine the magnitude of the influence of service quality and corporate image on customer satisfaction. The calculation results show a significant effect of service quality and company image on customer satisfaction. Recommendations from the study results suggest that optimizing consumer satisfaction felt by consumers should make consumers loyal to shipping service products so that consumers are reluctant to switch to using other shipping service products. Furthermore, with service improvements that make consumers loyal, consumers will likely be willing to pay more for the services they feel.